2009
DOI: 10.1134/s0021364009160115
|View full text |Cite
|
Sign up to set email alerts
|

Energy distributions of field emitted electrons from carbon nanosheets: Manifestation of the quantum size effect

Abstract: We emphasize the importance of experiments with voltage dependent field emission energy distribution analysis in carbon nanosheets. Our analysis shows the crucial influence of the band structure on the energy distribution of field emitted electrons in few-layer graphene. In addition to the main peak we found characteristic sub-peaks in the energy distribution. Their positions strongly depend on the number of layers and the inter-layer interaction. The discovery of these peaks in field emission experiments from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Graphene's few-layer counterparts have also recently been the subject of much interest, since this broader class of materials offers the potential for further control of electronic states by interlayer interactions (2)(3)(4)(5)(6). Indeed, theoretical investigations have predicted dramatic changes in the electronic properties in few-layer graphene (FLG) compared with single-layer graphene (SLG) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17): When two or more layers of graphene are present in ordered FLG, the characteristic linearly dispersing bands of the single layer are either replaced or augmented by pairs of split hyperbolic bands. These new bands correspond to fermions of finite mass, unlike the electrons present in SLG that behave as massless fermions.…”
mentioning
confidence: 99%
“…Graphene's few-layer counterparts have also recently been the subject of much interest, since this broader class of materials offers the potential for further control of electronic states by interlayer interactions (2)(3)(4)(5)(6). Indeed, theoretical investigations have predicted dramatic changes in the electronic properties in few-layer graphene (FLG) compared with single-layer graphene (SLG) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17): When two or more layers of graphene are present in ordered FLG, the characteristic linearly dispersing bands of the single layer are either replaced or augmented by pairs of split hyperbolic bands. These new bands correspond to fermions of finite mass, unlike the electrons present in SLG that behave as massless fermions.…”
mentioning
confidence: 99%
“…It has been found that CNSs have good field emission characteristics with promising applications in vacuum microelectronic devices [6][7][8]. Our theoretical analysis revealed the crucial influence of the band structure on the field emission characteristics of CNSs, in particular, on the energy distribution of field emitted electrons [9]. In that consideration we have explored a planar FN-like model based on the independent channel method suggested recently in [10].…”
mentioning
confidence: 84%
“…A theoretical study has shown that due to quantization of electron momentum, emission from graphene sheets follow the ln(J/F 3 ) ~ 1/F 2 law for dependence of emission current density, J, on applied electric field, F, in contrast to the conventional Fowler-Nordheim (FN) law of M a n u s c r i p t ln(J/F 2 ) ~ 1/F which is valid for three-dimensional materials [13]. Theoretical considerations which take into account a specific band structure of graphene and the field penetration effect also predict deviations from FN law [14] and reveal additional peaks in energy distribution of emitted electrons [15]. Moreover, relativistic [16] and electron interference [17,18] effects can in principle be identified in the study of FE patterns and currentvoltage characteristics of graphene emitters.…”
Section: Introductionmentioning
confidence: 93%